2019
DOI: 10.1029/2019gl085883
|View full text |Cite
|
Sign up to set email alerts
|

C‐Complex Asteroids: UV‐Visible Spectral Characteristics and Implications for Space Weathering Effects

Abstract: Space weathering effects on the rocky S-class asteroids are well understood. However, on the low-albedo C-complex asteroids, such as spacecraft targets Bennu and Ryugu, the situation is more complicated, especially due to a lack of spectral features throughout the visible-near infrared spectral region. Here we show, through a combination of observational data and laboratory data of carbonaceous chondrites, phyllosilicates, and mixtures, that the UV-visible spectral region is a diagnostic regime for studying sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…However, contrary to the bluing and darkening predicted from the production of graphitized carbon and magnetite, the formation of nanophase iron in low-albedo asteroids such as Bennu may have a reddening and brightening effect, owing to the higher reflectance of nanophase iron than that of the primitive materials found in carbonaceous meteorites (59). Space weathering trends observed on Bennu corroborate earlier studies (13,44) that found that primitive asteroids, though dark relative to the asteroid population, are brighter in the UV than their primitive meteorite counterparts-that is, they are spectrally bluer at shorter wavelengths. Ion bombardment of primitive low-albedo meteorites in the laboratory leads to spectral bluing and brightening (20).…”
Section: Mechanisms For Space Weathering On Bennusupporting
confidence: 81%
See 2 more Smart Citations
“…However, contrary to the bluing and darkening predicted from the production of graphitized carbon and magnetite, the formation of nanophase iron in low-albedo asteroids such as Bennu may have a reddening and brightening effect, owing to the higher reflectance of nanophase iron than that of the primitive materials found in carbonaceous meteorites (59). Space weathering trends observed on Bennu corroborate earlier studies (13,44) that found that primitive asteroids, though dark relative to the asteroid population, are brighter in the UV than their primitive meteorite counterparts-that is, they are spectrally bluer at shorter wavelengths. Ion bombardment of primitive low-albedo meteorites in the laboratory leads to spectral bluing and brightening (20).…”
Section: Mechanisms For Space Weathering On Bennusupporting
confidence: 81%
“…This absorption feature on Bennu has previously been attributed to magnetite (5), which is also detected in thermal emissivity spectra from OTES (7). However, this absorption feature could also result from graphitized carbon (44), and both magnetite and graphite are associated with space weathering (discussed further below).…”
Section: E and F)supporting
confidence: 52%
See 1 more Smart Citation
“…Continuous reflectance spectra of Bennu from the OSIRIS-REx Visible and InfraRed Spectrometer (OVIRS; Reuter et al 2018) at visible (VIS; 0.4-0.7 µm) and near-infrared (NIR; 0.7-4.3 µm) wavelengths reveal an absorption feature at 2.74 µm indicative of aqueous alteration of Mg-bearing phyllosilicates (Hamilton et al 2019;Hendrix and Vilas 2019). Similar 2.7-2.8 µm features are observed in CI and CM carbonaceous meteorites (Takir et al 2013), as well as in Fe-and Mgrich phyllosilicates such as saponite (McKee and Moore 1979;Barber 1981;Cloutis et al 2011aCloutis et al , 2011bHoward et al 2015;Donaldson Hanna et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2018) at visible (VIS; 0.4–0.7 µm) and near‐infrared (NIR; 0.7–4.3 µm) wavelengths reveal an absorption feature at 2.74 µm indicative of aqueous alteration of Mg‐bearing phyllosilicates (Hamilton et al. 2019; Hendrix and Vilas 2019). Similar 2.7–2.8 µm features are observed in CI and CM carbonaceous meteorites (Takir et al.…”
Section: Introductionmentioning
confidence: 99%